Constructing gene network for type 1 narcolepsy based on genome-wide association study and differential gene expression analysis (STROBE). Issue 18 (May 2020) - Ouyang, Hui; Wang, Shiying; Zheng, Qiwen; Zhang, Jun
Abstract : Abstract: Although many genes that affect narcolepsy risk have been identified, the interactions among these genes are still unclear. Moreover, there is a lack of research on the construction of the genetic network of narcolepsy. To screen candidate genes related to the onset of narcolepsy type 1, the function and distribution of important genes related to narcolepsy type 1 were studied and a gene network was constructed to study the pathogenesis of narcolepsy type 1. A case-control study (observational study) of 1075 Chinese narcoleptic patients and 1997 controls was conducted. The gene-sequencing data was analyzed using genome-wide association analysis. The candidate genes related to narcolepsy were identified by differential gene expression analysis and literature research. Then, the 28 candidate genes were input into the KEGG database and 32 pathway data related to candidate genes were obtained. A gene network, with the pathways as links and the genes as nodes, was constructed. According to our results, TNF, MHC II, NFATC2, and CXCL8 were the top genes in the gene network. TNF, MHC II, NFATC2, and CXCL8 are closely related to narcolepsy type I and require further study. By analyzing the pathways of disease-related genes and the network of gene interaction, we can provide an outlinefor the study of specific mechanisms of and treatments for narcolepsy.